Factors for Enhancement of Intracranial Atherosclerosis in High Resolution Vessel Wall MRI in Ischemic Stroke Patients - Woo, Na-Eun; Na, Han Kyu; Heo, Ji Hoe; Nam, Hyo Suk; Choi, Jin Kyo; Ahn, Sung Soo; Choi, Hyun Seok; Lee, Seung-Koo; Lee, Hye Sun; Cha, Jihoon; Kim, Young Dae (Frontiers in Neurology, 2020)
Introduction: High resolution vessel wall MRI (VW-MRI) has enabled to characterize intracranial atherosclerosis (ICAS). We studied to identify the factors for enhancement of ICAS in VW-MRI in patients with acute ischemic stroke. Methods: Consecutive patients with acute ischemic stroke or TIA who underwent VW-MRI between January 2017 and December 2017 were included. Enhancement on VW-MRI was defined as an increase in intensity on contrast-enhanced T1-weighted sequence. We compared the clinical and the radiologic findings between patients with wall enhancement and those without wall enhancement. Results: Of the 48 patients with ICAS, 28 patients revealed enhancement on VW-MRI. Patients with enhancement were more likely to have severe stenotic lesions and higher levels of total cholesterol, triglycerides, low-density cholesterol, Apo (b), and Apo (b)/Apo (a) lipoprotein ratio (p < .05). Multivariable analysis demonstrated that total cholesterol (OR: 5.378, 95% CI, 1.779 - 16.263), triglycerides (OR: 3.362, 95% CI, 1.008 - 11.209), low density lipoprotein cholesterol (OR: 4.226, 95% CI, 1.264 - 14.126), Apo (b) lipoprotein (OR: 3639.641, 95% CI, 17.854 - 741954.943) levels, and Apo (b)/Apo (a) lipoprotein ratio (OR, 65.514; 95% CI, 1.131 – 3680.239) were independently associated with enhancement of ICAS. High-density lipoprotein cholesterol and Apo (a) lipoprotein levels were not significantly different between the patients with wall enhancement and those without wall enhancement. Conclusions: The presence and severity of enhancement of ICAS was significantly associated with dyslipidemic conditions. These results suggest that strict lipid modification should be achieved for the management of ICAS.